Luper Borubung (Surface Area Of A Sphere, Cone, Cylinder) Project On The Surface Area Of Curved Sided Template Figures(Brsl) - Findia Ning Tyas, Dewi Kristika; Kulimbang, Elieser; Asri, Harits Pratama; Langoday, Maria Novita; Dori, Novita Nanianti (Abdi Masyarakat, 2025)
Mathematics learning on the topic BRSL, particularly the determination of surface area, is often hampered by the abstract nature of the concept and the lack of adequate visual representation. This condition has the potential to hinder students' conceptual understanding and mathematical reasoning abilities. We often find low student understanding and learning outcomes on this material. This luper borubung teaching aid is based on the urgency of developing learning aids that can bridge the gap between theory and visual reality. Students are introduced to the use of the luper borubung teaching aid, then given a test at the end of the activity containing BRSL material. The test results showed 71% of students in the good category. Students are enthusiastic, the learning atmosphere is more enjoyable and meaningful because they construct their own knowledge with the help of the luper borubung teaching aid.